Strategi Branding Daerah dan Pengaruhnya terhadap Minat Kunjungan Wisata Lokal: Systematic Literatur Review - Hasan, Moh.; Andriani, Nurita; Hasanah, Uswatun (SENTRI: Jurnal Riset Ilmiah, 2025)
The development of local tourism requires each region to have a strategy capable of building a strong and sustainable destination image and identity. One widely used approach is a regional branding strategy (destination branding), which focuses on fostering positive tourist perceptions of a region. This study aims to map the development of scientific studies related to regional branding strategies and their influence on local tourist visit interest through a systematic literature review approach based on bibliometric analysis. Data were collected using the Publish or Perish application sourced from Google Scholar and Scopus with a publication period of 2020–2025. A total of 993 journal articles that met the criteria were analyzed using VOSviewer software. The analysis techniques used included keyword co-occurrence, co-authorship, citation analysis, and bibliographic coupling. The analysis results indicate the existence of five main research clusters: destination branding, brand image and brand identity, tourist behavior (visit intention), digital tourism marketing, and local tourism development. The research findings also indicate a shift in research trends towards the use of digital media in regional branding strategies and an increased focus on local tourists. Furthermore, brand identity and destination branding have proven to be important factors in shaping tourist visit interest. This research provides theoretical contributions in mapping the direction of regional branding research as well as practical implications for local governments and tourism stakeholders in formulating more effective, innovative, and sustainable branding strategies.